Induction of autoimmune disease by adoptive transfer of an atypical NK cell subset - Voynova, Elisaveta (J Immunol, 2015)
Several mouse models of SLE, including FcγRIIB-KO and TLR7tg mice, develop an expansion of an atypical NK cell subset with functional similarity to cells referred as IKDCs or pre-mNKs in other systems. Here we show that atypical NKs purified from spleens of SLE-prone mice, and identified as NK1.1(+)CD11c(+)CD122(+)MHC-II(+), induce persistent autoimmune disease in an IFN-I and CD40L-dependent manner when transferred to WT mice. A single transfer of 4x10(6) NK1.1(+) cells from TLR7tg into WT induces a 2-week-long wave of inflammatory cytokines in the serum, a sustained increase in T cell activation and follicular helper cells for the following months, and a progressive expansion of dendritic cells, monocytes and granulocytes. Furthermore IL15 deficiency, which impedes development of NK cells, ameliorates the autoimmune pathology of TLR7tg mice. These results suggest that cells of the NK lineage can develop into cytokine producing/antigen-presenting cells that affect the priming and progression of systemic autoimmune disease.